Reciprocal transformations between music and architecture as a real-time supporting mechanism in urban design. (December 2016) - Parthenios, Panagiotis; Petrovski, Stefan; Chatzopoulou, Nicoleta; Mania, Katerina
The more complex our cities become, the more difficult it is for designers to use traditional tools for understanding and analyzing the inner essence of an eco-system such as the contemporary urban environment. Even many of the recently crafted digital tools fail to address the necessity for a more holistic design approach which captures the virtual and the physical, the immaterial and the material. Handling of massive chunks of information and classification and assessment of diverse data are nowadays more crucial than ever before. We see a significant potential in combining the fields of composition in music and architecture through the use of information technology. Merging the two fields has the intense potential to release new, innovative tools for urban designers. This article describes an innovative tool developed at the Technical University of Crete, through which an urban designer can work on the music transcription of a specific urban environment applying music compositional rules and filters in order to identify discordant entities, highlight imbalanced parts, and make design corrections. Our cities can be tuned.